PHYSICAL EVALUATION OF ETHANOLIC EXTRACT SHAMPOO RED GALANGAL AND OLIVE OIL WITH VARIATION OF SLS - Choirul Umi Haniyah; Indah Tri Lestari; Anggun Mahirotun (Jurnal PPI Dunia, 2021)
One of the plants created by Allah SWT that has many benefits is the rhizome of red galangal. Red galangal rhizomes contain essential oils consisting of methyl-sinamat, sineol, eugenol, kamfer, galangin, flavonoids, saponins and tannins. In addition to red galangal rhizomes, a natural ingredient that has many benefits is olive oil. In olive oil there are phenolic compounds that serve to antifungi, antibacterial, antioxidants. To formulate both plants, shampoo preparation innovations are made. In formulaizing shampoo preparations it is necessary to pay attention to the selection of surfactants. Sodium Lauryl Sulfate is a surfactant that has a large washing power, provides a lot of foam and a relatively low irritant effect. Utilization of red galangal rhizomes and olive oil with SLS comparison in shampoo is an alternative source of safer shampoo preparations for people with scalp infections. The observed dosage evaluation parameters are organoleptic, pH, viscosity, homogeneity and storage stability analyzed using ANOVA. The results of shampoo preparation quality testing obtained that formulations 2.3 and 4 in accordance with SNI standards and obtained the results of shampoo preparations are light brown, strong flavor with a pH of 5.2-5.3 at H0 and 8.2-8.6 on H12, with viscosity of 945-1534 cP at H0 and 154-3145 cP in H12.